Analisis Pengambilan Keputusan Pemilihan Negara Asal Impor Mesin dengan Metode TOPSIS Berdasarkan Data BPS 2018–2024 - Kinanti, Dindha Aprilia; Jumali, Muhamad Abdul; Firmansyah, Magnino Anggita (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify the most suitable country of origin for Indonesia’s machinery imports by analyzing import data from 2018 to 2024 using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. Secondary data obtained from the Central Bureau of Statistics (BPS) include import volume, CIF value, logistics costs, trade stability, and import growth. The analysis process consists of constructing the decision matrix, normalizing the data, assigning criterion weights, determining ideal solutions, and calculating preference values for each alternative country. The results indicate that China is the most optimal source of machinery imports, achieving the highest preference score due to its dominance in volume, economic value, supply consistency, and trade growth. South Korea and the “Others” category follow as strategic alternatives. Overall, the TOPSIS method proves effective in providing objective and measurable support for multi-criteria decision-making related to selecting import partner countries.